How do tax progressivity and household heterogeneity affect Laffer curves? - Hans A. Holter; Dirk Krueger; Serhiy Stepanchuk (Quantitative Economics, 2019)
How much additional tax revenue can the government generate by increasing the level of labor income taxes? In this paper, we argue that the degree of tax progressivity is a quantitatively important determinant of the answer to this question. To make this point, we develop a large scale overlapping generations model with single and married households facing idiosyncratic income risk, extensive and intensive margins of labor supply, as well as endogenous accumulation of human capital through labor market experience. We calibrate the model to U.S. macro, micro, and tax data and characterize the labor income tax Laffer curve for various degrees of tax progressivity. We find that the peak of the U.S. Laffer curve is attained at an average labor income tax rate of . This peak (the maximal tax revenues the government can raise) increases by if the current progressive tax code is replaced with a flat labor income tax. Replacing the current U.S. tax system with one that has Denmark' s progressivity would lower the peak by . We show that modeling the extensive margin of labor supply and endogenous human capital accumulation is crucial for these findings. With joint taxation of married couples (as in the U.S.), higher tax progressivity leads to significantly lower labor force participation of married women and substantially higher labor force participation of single women, an effect that is especially pronounced when future wages of females depend positively on past labor market experience.
Keywords: E62; H20; H60; 330; Laffer curve; progressive taxation; heterogeneous households